The Determinants of Company Value and its Impact on the Jakarta Composite Index (JCI) of Energy Sector Companies Listed on the Indonesian Stock Exchange (IDX) 2017–2023 - Handayani, Sri Sunarti; Salim, M. Noor (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research objectives to determine Intellectual Capital (VAIC), Growth Opportunity (GO) and Cash Holding (Cash) effect toward the Jakarta Composite Index (JCI) mediated by Company Value (PBV). The population are energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2017-2023 period. This study used 74 energy companies but only 16 companies meet the sample criteria. The data used in this research are secondary data obtained from the Indonesian Stock Exchange (www.idx.co.id) and from the websites of each company. The analytical method used in this research is descriptive statistical analysis, path analysis and Sobel analysis. The results of this study indicate that the variables of intellectual capital, growth opportunity, cash holding, and company value have a positive and significant effect on the JCI. Meanwhile, the intellectual capital, growth opportunity and cash holding have a positive and significant effect on the company value. Company value as an intervening variable is able to mediate the influence of intellectual capital, growth opportunity and cash holding on JCI.